The Concept of Zakat on Income in Malaysia and Its Beginning of Implementation - Muhsin Nor Paizin (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2021)
One of zakat’s objectives is to keep the economic division in society to a minimum. It is to foster a just and equitable economic environment in society, in which the wealthy do not become excessively wealthy, and the poor do not become more destitute. Thus, implementing zakat on income is appropriate and consistent with efforts to accomplish this goal. In general, the management of zakat on income in Malaysia entails fatwas and the decisions they entail, and how they are implemented. This study used the historical method to present the backgrounds. The discussions show that zakat on income has been vigorously implemented in Malaysia. They began with the efforts necessary to enact it and end with its integration into the implementation system. Thus, it hopes to yields positive results in terms of zakat collection and can be used by the asnaf to improve their living standards.